2021
DOI: 10.1021/jacs.1c04149
|View full text |Cite
|
Sign up to set email alerts
|

Metal Ion Control of Photoinduced Electron Spin Polarization in Electronic Ground States

Abstract: Both the sign and intensity of photoinduced electron spin polarization (ESP) in the electronic ground state doublet (2S0/D0) of chromophore-radical complexes can be controlled by changing the nature of the metal ion. The complexes consist of an organic radical (nitronyl nitroxide, NN) covalently attached to a donor–acceptor chromophore via a m-phenylene bridge, (bpy)­M­(CAT-m-Ph-NN) (1) (bpy = 4,4′-di-tert-butyl-2,2′-bipyridine, M = PdII (1-Pd) or PtII (1-Pt), CAT = 3-tert-butylcatecholate, m-Ph = meta-phenyle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
75
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(75 citation statements)
references
References 43 publications
(63 reference statements)
0
75
0
Order By: Relevance
“…Recently, we demonstrated that despite the short 2 T 1 excited state lifetime and absence of intermolecular collisions, strong ground state ESP can be generated in (bpy)Pt(CAT- m -Ph-NN) ( mPh-Pt , NN = nitronylnitroxide radical). 16 The intensity of the photoinduced ESP in mPh-Pt was also shown to be dramatically altered by changing the metal ion from Pt to Pd in what are otherwise identical complexes. 16 In the present work, we show that the nature of the ground state ESP is also related to the magnitude of the excited state chromophore-radical antiferromagnetic exchange ( J SQ-NN (= 2 J CR ) Fig.…”
Section: Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…Recently, we demonstrated that despite the short 2 T 1 excited state lifetime and absence of intermolecular collisions, strong ground state ESP can be generated in (bpy)Pt(CAT- m -Ph-NN) ( mPh-Pt , NN = nitronylnitroxide radical). 16 The intensity of the photoinduced ESP in mPh-Pt was also shown to be dramatically altered by changing the metal ion from Pt to Pd in what are otherwise identical complexes. 16 In the present work, we show that the nature of the ground state ESP is also related to the magnitude of the excited state chromophore-radical antiferromagnetic exchange ( J SQ-NN (= 2 J CR ) Fig.…”
Section: Introductionmentioning
confidence: 94%
“… 16 The intensity of the photoinduced ESP in mPh-Pt was also shown to be dramatically altered by changing the metal ion from Pt to Pd in what are otherwise identical complexes. 16 In the present work, we show that the nature of the ground state ESP is also related to the magnitude of the excited state chromophore-radical antiferromagnetic exchange ( J SQ-NN (= 2 J CR ) Fig. 2A ), which can be controlled by tailored bond torsions that reduce π-system mediated superexchange coupling.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations